Про про профессии - Борисова Наталья (Другой, другие, о других. Детский проект Людмилы Улицкой, 2012)
Экземпляры: аб. (20140916) / Инвентарный номер: 56036 / Цена: / Сис.шифр: 71.04 / Авт.знак: Б 82 / ГРНТИ: 13.01 / ББК: 71.04^VLBC/RL